師資培育學系發展補教事業經營人力之個案研究 A Case Study of Department of Teacher Education in the Development of Training Human Resources for Cram School Management - 簡梅瑩 Chien, Mei-Ying; 潘文福 Pan, Wen-Fu (National Changhua University of Education, 2012)
此研究旨在透過對補教經營方式及人力需求之探討，提供師資培育學系發展相關人力培訓內容及作法之參考。此研究共納入五所補習班及七位大學生為研究對象；學生分別在這五所補習班進行為期三個月的實習。研究者以質性個案研究為策略，採用之資料收集方法包括：與補習班經營者及學生之半結構錄音訪談、學生省思週誌與實習機構個案報告撰寫、與學生小組之討論、本校院與系課程相關資料之收集。研究資料分析結果如下： （1）補習班經營著重在能確實回應家長及學童的個別需求；因此，有關行政管理及教學人力的用才條件，除強調個人具備有相關的訓練及經驗，更注重其是否具備良好的溝通技巧。 （2）多數實習學生在輔導學童學科學習的過程中，感到自我在學科教學能力上的不足，特別是國語及數學；而針對如何幫助學童專注學習，特別是有學習困難的學童，也讓多數學生感到困惑及無助。 （3）師資培育學系在發展補教人力的課程規劃，需致力增能學生在主要學科的教學知能，及有關兒童心理與發展、學生輔導、人際關係、組織管理、及市場行銷等專業知能；在培訓作法部分，則需致力提供學生參與實際場域的機會，以能幫助學生進行知識與實務的連結。 This study was aimed to explore the management of cram schools and their requirements for human resources in Taiwan, and how the department of teacher education could adapt its training for helping students to enroll in this work sector. There were 5 cram schools and 7 university students participating in this research; students were placed individually in these 5 cram schools for the practicum of three months. A qualitative case study approach was conducted using interviews with cram school managers and students, students' reflective diary and case-study report, group discussions with students, and document collection and analysis. The results indicated: 1. The management of cram schools is mainly concerned with meeting parents' and children's needs, so the staff is required to have qualified experiences and good communication skills; 2. Most students feel inadequate about assisting children's learning of core subjects such as Chinese and Mathematics and those with learning difficulties; 3. The adaptation of teacher training curriculum should focus on enhancing students' teaching knowledge and skills as well as providing them with real-life experience for applying the knowledge.